THE THE EFFECT OF LAUGHTER THERAPY ON BLOOD PRESSURE IN OLDER PEOPLE WITH HYPERTENSION - Paramita Ratna Gayatri; Septina Margaretta, Sheylla; Nur Pratiwi , Wahyu (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The aged are more susceptible to a number of health issues as they age, including disruptions in their physiological processes. Health problem which commonly experienced by the older people is Hypertension. Laughter therapy is one non-pharmacological strategy that can be used with senior hypertensive patients. This research was conducted to determine the effect of laughter therapy on changes in blood pressure in elderly people with hypertension. A pretest-posttest nonequivalent groups design was employed in this quasi-experimental study design. In this study, 23 participants in each group, which treatment group (get Laughter Therapy) and control group (didn’t get Laughter Therapy). The findings of the Wilcoxon test indicate that ρ = 0.000, where ρ < α (0.05), indicates that H1 is accepted, indicating that laughter therapy has an impact on changes in blood pressure in older adults with hypertension. Keywords : Hypertension, Older People, Laughter Therapy